Taxonomic study of the genus Kapsa Dworakowska with a new subgenus, and new combinations and records for Tautoneura Anufriev (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) - Yang, Meixia; Cao, Yanghui; Zhang, Yalin (Zootaxa, 2013)
The genus Kapsa Dworakowska is redescribed and a new subgenus Kapsa (Rigida) Cao & Zhang is established to include thirteen species, a key to males of the subgenus is provided, and eight new species from China are described and illustrated: Kapsa aculeiformis, K. apicispina, K. brevis, K. explanata, K. furcata, K. imminuta, K. megaprocessa and K. serrata spp. nov.. Based on detailed study of previously described species, Kapsa yanheensis Song & Li, 2012 is considered a synonym of Tautoneura albida (Dworakowska, 1970). Four species previously placed in Kapsa are transferred to Tautoneura Anufriev: Tautoneura decorata (Dworakowska, 1981), T. diasonica (Chiang & Knight, 1990), T. elscinta (Chiang & Knight, 1990) and T. puerensis (Song & Li, 2012). K. alba Dworakowska, 1981 and T. ahmedi Dworakowska, 1977 are reported for the first time fromChina.